Human Immunodeficiency Virus (HIV) Genetic Diversity Informs Stage of HIV-1 Infection Among Patients Receiving Antiretroviral Therapy in Botswana. (2nd June 2021) - Ragonnet-Cronin, Manon; Golubchik, Tanya; Moyo, Sikhulile; Fraser, Christophe; Essex, Max; Novitsky, Vlad; Volz, Erik
Abstract: Background: Human immunodeficiency virus (HIV)-1 genetic diversity increases during infection and can help infer the time elapsed since infection. However, the effect of antiretroviral treatment (ART) on the inference remains unknown. Methods: Participants with estimated duration of HIV-1 infection based on repeated testing were sourced from cohorts in Botswana (n = 1944). Full-length HIV genome sequencing was performed from proviral deoxyribonucleic acid. We optimized a machine learning model to classify infections as < or >1 year based on viral genetic diversity, demographic, and clinical data. Results: The best predictive model included variables for genetic diversity of HIV-1 gag, pol, and env, viral load, age, sex, and ART status. Most participants were on ART. Balanced accuracy was 90.6% (95% confidence interval, 86.7%–94.1%). We tested the algorithm among newly diagnosed participants with or without documented negative HIV tests. Among those without records, those who self-reported a negative HIV test within <1 year were more frequently classified as recent than those who reported a test >1 year previously. There was no difference in classification between those self-reporting a negative HIV test <1 year, whether or not they had a record. Conclusions: These results indicate that recency of HIV-1 infection can be inferred from viral sequence diversity even among patients on suppressive ART. Abstract : A single HIV virus is usually transmitted. HIV then replicates, making errors, and over time genetic diversity increases. We found that time since HIV infection can be estimated from within-patient HIV genetic diversity, even when patients are on treatment.